Formation of Cytoplasmic Actin-Cofilin Rods is Triggered by Metabolic Stress and Changes in Cellular pH - Ishikawa-Ankerhold, Hellen C.; Kurzbach, Sophie; Kinali, Arzu S.; Müller-Taubenberger, Annette (Frontiers in Cell and Developmental Biology, 2021)
Actin dynamics plays a crucial role in regulating essential cell functions and thereby is largely responsible to a considerable extent for cellular energy consumption. Certain pathological conditions in humans, like neurological disorders such as Alzheimer’s disease or amyotrophic lateral sclerosis (ALS) as well as variants of nemaline myopathy are associated with cytoskeletal abnormalities, so-called actin-cofilin rods. Actin-cofilin rods are aggregates consisting mainly of actin and cofilin, which are formed as a result of cellular stress and thereby help to ensure the survival of cells under unfavorable conditions. We have used Dictyostelium discoideum, an established model system for cytoskeletal research to study formation and principles of cytoplasmic actin rod assembly in response to energy depletion. Experimentally, depletion of ATP was provoked by addition of either sodium azide, dinitrophenol, or 2-deoxy-glucose, and the formation of rod assembly was recorded by live-cell imaging. Furthermore, we show that hyperosmotic shock induces actin-cofilin rods, and that a drop in the intracellular pH accompanies this condition. Our data reveal that acidification of the cytoplasm can induce the formation of actin-cofilin rods to varying degrees and suggest that a local reduction in cellular pH may be a cause for the formation of cytoplasmic rods. We hypothesize that local phase separation mechanistically triggers the assembly of actin-cofilin rods and thereby influences the material properties of actin structures.